Misinformation – Foreign Language Teaching Problems Resulting from the Perception of Reality and Communication Culture - Matulewska, Aleksandra; Wasielewska, Magdalena (Investigationes Linguisticae, 2004)
This paper discusses the problems connected with mistranslation of idioms, emotionally marked expressions and false cognates. The purpose of the paper is to present the main foundations of misinformation and communication noise which result from the fact that foreign language learners are unaware of (i) the existence of false cognates, and (ii) the differences between the literal meaning and the implied one as far as emotionally marked expressions and idioms are concerned. It often causes communication breakdowns and equivalence deficiency in interlingual communication. The authors give examples of such idioms, emotionally marked expressions and false cognates and discuss the communicative aspects connected with such misinformation. Finally, the paper includes the suggestions of techniques which may be used by foreign language teachers in order to make the language learners aware of those problems. What follows at the end of the paper is a collection of four activities for English learners which are designed to teach them how to distinguish those problematic words and expressions and to make them understand the impact of communication noise on the messages produced by them.